E-literacy-adoption model and performance of women-owned SMEs in Southwestern Nigeria - Ojinga G. Omiunu (Journal of Global Entrepreneurship Research, 2019)
The study investigates the moderating effect of e-literacy and business information strategy on the relationship between ICT adoption and performance of women-owned SMEs in Southwestern Nigeria. The theories of information technology trilogy by (J Strateg Inf Syst 10:77-99, 2001) coupled with the ICT literacy of (MediaSmarts, Digital Literacy Funadamentals, Canada's Centre for Digital and Media Literacy MediaSmarts, 2017) which in this study is conceptualized as e-literacy were adapted, and five hypotheses were formulated towards proposing an e-literacy-adoption model for enhanced SMEs' performance. The study adopted the correlational survey research design and consists of women-owned SMEs in Southwestern, Nigeria. A multi-stage sampling was employed in the study, and a sample size of 240 women-owned SMEs was drawn. However, 236 were retrieved, giving a 94.4% response rate. The questionnaire was used to obtain information, and the correlation analysis was used to analyze the data obtained. The result of the study revealed that e-literacy and business information strategy are significant to the adoption of ICT for effective performance among women-owned SMEs in Nigeria. The study recommends that governments and various NGOs committed to enhancing the growth and development of women-owned SMEs in Nigeria should provide necessary grants and sponsorship towards providing necessary ICT workshops and trainings that could enhance women-owned SMEs' e-literacy and skills and also the adoption of ICT towards a better performance.
Keywords: 650; E-literacy-adoption model; Performance of women-owned SMEs; Women-owned SMEs in Nigeria